USING REPETITIVE WRITING TO IMPROVE SEVENTH GRADE STUDENTS’ VOCABULARY MASTERY AT SMP GPDI BEREA TONDANO - Felro Mokorimban; Paula Rombepajung; Tirza Kumayas (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
In learning a language, there are some variant levels from the low to the advance level where people going to learn from the simple to the more complex aspects of a language. One of the basic aspects is the vocabulary. This research aims to study a method called “repetitive writing” to see the effectivity and efficiency in improving students’ vocabulary mastery. This research took place in SMP GPdI Berea Tondano on the seventh grade students. This research used a quantitative approach in collecting the data and used pre-experimental research design in the form of “one group pre-test post-test design” and used mean formula for data analysis. The research instrument used a multiple choices test which containts of two main part: translation and definition. There were two main data, the pre-test score (before the treatment) and the post-test score (after the treatment). The result showed that the score after the treatment is higher with the mean score of 86,5, compared to the mean score before treatment which was 62, which indicates that there were some improvements in students vocabulary performance. From the result, it can be concluded that the repetitive writing method is effective and efficient so thus it can be introduced by teacher and applied by students to improve students vocabulary mastery. It is suggested to the teacher to use the repetitive writing method in learning process in order to help the students in their activity of mastering vocabulary